2020
DOI: 10.1105/tpc.20.00562
|View full text |Cite
|
Sign up to set email alerts
|

Soybean DICER-LIKE2 Regulates Seed Coat Color via Production of Primary 22-Nucleotide Small Interfering RNAs from Long Inverted Repeats

Abstract: Soybean DCL2 favors long inverted repeat-derived double-stranded RNA as its substrate, and generates primary 22-nt siRNAs to regulate seed coat color and silence transposable elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…There is potential for similar outcomes in the many other species carrying EPRVs including bitter orange, rice, lucky bamboo, Dahlia, pineapple, grapes, poplar and fig 10 . In sugar beet 15 and soybean 16 the EPRV are associated with 22nt sRNAs as in Solanum. This sRNA-based mechanism involving EPRVs could modify gene expression in hybrid populations of many species and increase the range of traits available for selection in natural evolution or breeding for agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…There is potential for similar outcomes in the many other species carrying EPRVs including bitter orange, rice, lucky bamboo, Dahlia, pineapple, grapes, poplar and fig 10 . In sugar beet 15 and soybean 16 the EPRV are associated with 22nt sRNAs as in Solanum. This sRNA-based mechanism involving EPRVs could modify gene expression in hybrid populations of many species and increase the range of traits available for selection in natural evolution or breeding for agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the role of the DCL2-dependent 22-nucleotide siRNA (derived from long inverted repeats) regulating chalcone synthase ( CHS ) genes attributing seed coat colour in soybean, a study conducted by Jia et al (2020) [ 176 ] revealed that CRISPR/Cas9-driven loss-of-function mutants of DCL2 ( GmDCL2a and GmDCL2b ) caused changes in seed coat colour from yellow to brown in Gmdcl2a/2b mutants in soybean. Thus, this study confirmed that DCL2 controls soybean seed coat colour via generating siRNA from long inverted repeats [ 176 ].…”
Section: Regulatory Role Of Ncrnas For Shaping Developmental Processes In Legume Speciesmentioning
confidence: 99%
“…Soybeans are available in a range of colors from yellow, green, brown, and black, to mottled [ 7 ]. Physiological and genetic studies indicate that the color variation is due to the difference in the accumulation of pigment-stimulating metabolites [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%